Layout Evaluation at PT Juyomi Sinar Labuan Using the Systematic Layout Planning Method - Nur' Asia; Sulaeman Miru; Umar Syarifuddin; Fatlina Zainuddin; Syamsuddin Syamsuddin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to evaluate and improve the efficiency of the facility layout at PT Juyomi Sinar Labuan using the Systematic Layout Planning (SLP) method. The research employs a quantitative approach combined with limited qualitative analysis through field observations, measurements of material flow distances, cycle time calculations, and interviews with key personnel. The results indicate that the existing layout, although functionally aligned with the production sequence, still exhibits inefficiencies, as reflected in a total Load Distance of 302 meters and a material handling cycle time of 5.05 minutes. These inefficiencies are primarily caused by the recirculation flow between the 2 Deck Screen and the Kun Crusher, which creates a backtracking pattern and increases material movement distance. The application of the SLP method produces a more compact and structured layout without requiring major equipment relocation. The proposed layout reduces the Load Distance to 278 meters and the cycle time to 4.65 minutes, indicating improvements of approximately 8% and 7.9%, respectively. These findings demonstrate that optimizing material flow configuration can significantly improve operational efficiency, streamline workflow, and enhance production effectiveness. This study contributes to the limited literature on SLP application in open-space, heavy-equipment-based industries and provides practical recommendations for incremental layout improvement.